Impact of untreated high blood pressure on renal function tests at initial diagnosis of Hypertension - Syed, Sadiqa; Zia ul Islam; Qureshi, Masood A (International Journal of Endorsing Health Science Research, 2014)
Background: Pakistani population is at higher risk of developing hypertensive complications at a younger age, resulting from undiagnosed and untreated hypertension (HTN). High cost of medical care is a barrier to early detection and assessment of end organ damage as well as physicians are disinclined to adopt more aggressive therapeutic management to improve blood pressure control. A cross sectional study was planned to determine the effect of high blood pressure on renal function tests in a random population aged 25-50 year, at initial diagnosis of hypertension. Methods: The study was conducted on total 276 subjects; 201selected from five general practitioners clinics in Karachi and were classified into pre hypertensive, and hypertensive stages I and II on the basis of 7th JNC report. Two BP readings were taken half an hour apart. A blood sample was drawn for measurement of serum urea, creatinine and a dipstick test was done to check protein in urine. The results were compared with 75 control, normotensive subjects. The percentage, mean and Standard deviation were computed. ANOVA was performed to compare four study groups and LSD test was applied to compare pair-wise group. Pearson’s correlation was applied to find out association of renal function with stages of hypertension. Results: The mean urea and creatinine levels were on higher normal side in HTN stages-I and II (39.91±8.51 and 1.72±0.54 in stage-I and 44.51±9.93 and 1.91±0.88 in stage-II respectively). The frequency of proteinuria was also more in these groups, indicating declining renal function in these patients as compared to control and prehypertension groups. Conclusion: Subjects diagnosed with stage I and II HTN showed evidence of subclinical renal damage, along with the presence of proteinuria at the time of diagnosis.